(3GdEHGfI Yf CUhd GdOjGfIs - (3CHh GdMSf Ydj Hf ESeGYjd GdGTYQjs
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdCMO GdYRjR aUd ai EHGfI bhd Cgd GdRjZ hGdHYOi CeG HYO aEf cKjQkG ef GdRGFZjf Yf GdMb ef GdeYJRdI hCgd GdbOQ eGdJ Hge CghGFge s
(3BNQgG (B:s
(3hcPdc eG LQi Hjf eYGhjI hYdi QVi Gddg YfgeG cGf Ydi JChjd hELJgGO bO bdfG ai GdCHQGQ bhdkG hNjQkG hGdMeO ddg ChdkG hBNQkG BNQ GdcJGH hGdMeO ddg hMOg s
(3HChdg Jedc eDQN SfI (B1154(3g`s
(3HgG fXGe GdJYbjHIs
(3aQZ GdeDda ef JCdjag SfI (B84 (3g`s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs